Strategi Penguatan Visi, Misi, Dan Nilai Organisasi untuk Meningkatkan Kinerja Dan Identitas Lembaga - Ida Kusumawati; Hafidatun Nabila (Edu Journal Innovation in Learning and Education, 2026)
This study aims to analyze the strengthening of the organization's vision, mission, and values in improving the performance and identity of the institution at MTs Miftahul Hasanah Gading. This research uses a descriptive qualitative approach with a case study category. Data collection techniques included observation and interviews, while data analysis utilized the Miles and Huberman model for data presentation, data reduction, and drawing conclusions. The results of this study indicate that the strengthening of the organization's vision, mission, and values is still not optimal. The formulation stage was semi-participatory, while the internalization of values was carried out normatively without a structured plan. However, exemplary leadership is a crucial factor in strengthening the implementation of organizational values. The results of these improvements can be seen in improved performance and the beginning of the realization of the institution's identity in the community. This study emphasizes that strengthening the vision, mission, and work values requires more integrated, cohesive, and sustainable mentoring to achieve maximum results in the institution's performance and identity.